Improving Students' Numerical Literacy Through Project-Based Learning (PjBL) in Pascal Programming Course - Muhammad Taufik; Joni Rokhmat; Muhammad Zuhdi (Postgraduate Program, University of Mataram, 2023)
Numerical literacy, the ability to interpret and apply numerical data, is crucial for success in various fields, including computer science. Traditionally, Pascal programming courses rely on passive learning methods, hindering students' development of numeracy skills. This study investigated the effectiveness of project-based learning (PjBL) in improving numeracy literacy among 46 Physics Education students enrolled in a Pascal programming course at Mataram University in Indonesia. The PjBL approach involved real-world projects requiring students to apply and analyze numerical data within their programming tasks. Findings revealed significant improvements in numeracy literacy, with success rates of 97% for short analysis, 87% for medium analysis, and 46% for long analysis. Overall, the average learning outcome was 84 out of 100, demonstrating the potential of PjBL as an effective learning model for enhancing numeracy skills in programming contexts. Further research is encouraged to refine PjBL implementation models and optimize its impact on numeracy literacy in STEM education.